Olfactory bulb α-synucleinopathy has high specificity and sensitivity for Lewy body disorders - Beach, Thomas G.; White, Charles L.; Hladik, Christa L.; Sabbagh, Marwan N.; Connor, Donald J.; Shill, Holly A.; Sue, Lucia I.; Sasse, Jeanne; Bachalakuri, Jyothi; Henry-Watson, Jonette; Akiyama, Haru; Adler, Charles H. (Acta neuropathologica, 2009)
Involvement of the olfactory bulb by Lewy-type α-synucleinopathy (LTS) is known to occur at an early stage of Parkinson’s disease (PD) and Lewy body disorders and is therefore of potential usefulness diagnostically. An accurate estimate of the specificity and sensitivity of this change has not previously been available. We performed immunohistochemical α-synuclein staining of the olfactory bulb in 328 deceased individuals. All cases had received an initial neuropathological examination that included α-synuclein immunohistochemical staining on sections from brainstem, limbic and neocortical regions, but excluded olfactory bulb. These cases had been classified based on their clinical characteristics and brain regional distribution and density of LTS, as PD, dementia with Lewy bodies (DLB), Alzheimer’s disease with LTS (ADLS), Alzheimer’s disease without LTS (ADNLS), incidental Lewy body disease (ILBD) and elderly control subjects. The numbers of cases found to be positive and negative, respectively, for olfactory bulb LTS were: PD 55/3; DLB 34/1; ADLS 37/5; ADNLS 19/84; ILBD 14/7; elderly control subjects 5/64. The sensitivities and specificities were, respectively: 95 and 91% for PD versus elderly control; 97 and 91% for DLB versus elderly control; 88 and 91% for ADLS versus elderly control; 88 and 81% for ADLS versus ADNLS; 67 and 91% for ILBD versus elderly control. Olfactory bulb synucleinopathy density scores correlated significantly with synucleinopathy scores in all other brain regions (Spearman R values between 0.46 and 0.78) as well as with scores on the Mini-Mental State Examination and Part 3 of the Unified Parkinson’s Disease Rating Scale (Spearman R −0.27, 0.35, respectively). It is concluded that olfactory bulb LTS accurately predicts the presence of LTS in other brain regions. It is suggested that olfactory bulb biopsy be considered to confirm the diagnosis in PD subjects being assessed for surgical therapy.